2011
DOI: 10.1002/app.34099
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of enhanced urea–formaldehyde resin microcapsules doped with nanotitania

Abstract: Urea-formaldehyde (UF) resin microcapsules doped with TiO 2 nanoparticles were prepared by in situ polymerization, and the properties of the microcapsules, such as the surface morphologies, thermal properties, and chemical elemental composition, were measured by optical microscopy, scanning electron microscopy, thermogravimetric analysis, and energy-dispersive X-ray spectrometer analysis. The effects of the presence of ammonium chloride and its concentration and the concentrations of UF resin prepolymer and Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…The results indicated that nano-SiO 2 can keep the structural integrity of the microcapsules. Similar results were found in the research of Niu et al [40]. The micrographs also showed that pores and cracks were not present on the surface of the microcapsules, which contributed to the protection of the core material by decreasing oxygen diffusion into the microcapsules [34].…”
Section: Resultssupporting
confidence: 89%
“…The results indicated that nano-SiO 2 can keep the structural integrity of the microcapsules. Similar results were found in the research of Niu et al [40]. The micrographs also showed that pores and cracks were not present on the surface of the microcapsules, which contributed to the protection of the core material by decreasing oxygen diffusion into the microcapsules [34].…”
Section: Resultssupporting
confidence: 89%
“…The DJ is an aromatic mixture containing The other procedures about emulsification and polymerization were similar to the fabrication of the pure MF shell microcapsules[35]. Eventually, most of the Al 2 O 3 nanoparticles were embedded into the MF shell[37,38].…”
mentioning
confidence: 99%
“…Therefore, despite the high strength and low‐cost of UF, this drawback largely limits its usage. Many attempts have been made to improve the toughness of UF resins . One approach is reducing the mole ratio of formaldehyde/urea, however, this leads to a decrease of crosslinking degree and thus, inferior performance of the resin, regarding its mechanical strength and water resistance .…”
Section: Introductionmentioning
confidence: 99%